Ibn Sina dan Ibn Rusyd dalam Pengembangan Sains Modern di Barat - Hindami, Qoidy Hilman; Yusuf, Mochamad (Universitas Yudharta Pasuruan, 2023)
Currently, the West is the world's reference in the field of science and technology. The Western world did not suddenly find its glory as it is today, but it all went through a very long process until it met the works of several great Islamic figures. This long process involved two great Islamic figures such as Ibnu Sina and Ibnu Rusyd. In this article the author will discuss the process of development of modern science in the West and will also review the magnitude of the influence Ibn Sina and Ibn Rusyd on the Western world. Without these two figures, perhaps the Western world would not have found its glory in the field of science. In this research, readers will find answers to questions 1) What is the role of Ibn Rushd and Ibn Sina in the development of modern science? 2) What is the epistemological relationship between the thoughts of Ibn Rushd, Ibn Sina and Modern science? 3) What are the thoughts and works of Ibn Rushd and Ibn Sina? This research uses qualitative methods with analytical descriptive characteristics.